Stroke Case for First-Year Medical Students - Laura Welke; Mary Moore; Agnes Laville; Phil Conran (Association of American Medical Colleges, 2010)
Abstract This resource is a stroke case for first-year medical students. It provides students with the opportunity to work effectively to describe the abnormal biochemical, vascular, neurological, and pathological processes that produced the specific problem in the clinical application exercise. Students are required to discuss and understand basic neural orientation and brain sectional anatomy. Students also analyze blood test results to determine normal and/or abnormal lipid values. They also utilize vascular histology and central nervous system blood supply knowledge to determine the possible pathological effects that may result from any abnormal lipid levels. Finally, they discuss the microscopic vascular pathology that may result from the clinical presentation and give a probable diagnosis for their findings. The case smoothly incorporates histological and biochemical knowledge related to the clinical presentation and structural changes that would be exhibited in an individual suffering a stroke. Students begin to think across disciplines to produce a list of differential diagnoses based on lab data and clinical presentation of a patient.